The Pichia pastoris peroxisomal protein PAS8p is the receptor for the C-terminal tripeptide peroxisomal targeting signal. - Terlecky, S R (1995)
The peroxisomal targeting signal 1 (PTS1), consisting of a C-terminal tripeptide (SKL and variants), directs polypeptides to the peroxisome matrix in evolutionarily diverse organisms. Previous studies in the methylotrophic yeast Pichia pastoris identified a 68 kDa protein, PAS8p, as a potential component of the PTS1 import machinery. We now report several new properties of this molecule which, taken together, show that it is the peroxisomal PTS1 receptor. (i) PAS8p is localized to and tightly associated with the cytoplasmic side of the peroxisomal membrane, (ii) peroxisomes of wild-type, but not of pas8 delta (null) mutant, P.pastoris cells bind a PTS1-containing peptide (CRYHLKPLQSKL), (iii) CRYHLKPLQSKL can be cross-linked to PAS8p after binding at the peroxisome membrane and (iv) purified PAS8p binds CRYHLKPLQSKL with high affinity (nanomolar dissociation constant). In addition, the tetratricopeptide repeat (TPR) domain of PAS8p is identified as the PTS1 binding region.